De paradoxen van “Latijns-Amerikaans Handboek” van Kristien Hemmerechts en zijn vertaling - Vermeiren, Hildegard (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
“Latijns-Amerikaans Handboek” by Kristien Hemmerechts proves that short stories as a literary genre are able to portray a complex multilingual adven-ture in just a few pages. The writer makes use of a Latin American setting to give shape to the galloping loss of identity of a young Flemish man, travel-ling with his girlfriend through the Peruvian Quechua world. The enormous cultural distance between the Flemish and Quechua cultures makes his metamorphosis as absurd as it is comprehensible. Because of her emotional faithfulness, his girlfriend does not intervene and as a result the young man dies. The translation of this short story in its turn poses the problem of the loss of that same cultural identity. In the name of his professional faithful-ness, however, it is the duty of the translator to intervene in time and to save from death the original cultural identity of the story.